Prokaryotic Community Structure and Metabolisms in Shallow Subsurface of Atacama Desert Playas and Alluvial Fans After Heavy Rains: Repairing and Preparing for Next Dry Period - Fernández-Martínez, Miguel Ángel; dos Santos Severino, Rita; Moreno-Paz, Mercedes; Gallardo-Carreño, Ignacio; Blanco, Yolanda; Warren-Rhodes, Kimberley; García-Villadangos, Miriam; Ruiz-Bermejo, Marta; Barberán, Albert; Wettergreen, David; Cabrol, Nathalie; Parro, Víctor (Frontiers in Microbiology, 2019)
Atacama Desert, the oldest and driest desert on Earth, displays significant rains only once per decade. To investigate how the microbial communities take advantage of these wet events, we carried out a geomicrobiological study few days after a heavy rain event in 2015. Different physicochemical and microbial community analyses were conducted on samples collected from playas and an alluvial fan from surface, 10, 20, 50 and 80 cm depth. A water content peaks were measured in 10 and 20 cm depth samples (from 1.65% to 4.1% w/w maximum values) while, in general, main anions such as chloride, nitrate, and sulphate concentrations increased with depth with maximum values of 13 to 1125 ppm, 168 to 10,109 ppm and 9,904 to 30,952 ppm, respectively. Small organic anions such as formate and acetate were also measured with maximum concentrations from 2.61 to 3.44 pm and 6.73 to 28.75 ppm, respectively. Microbial diversity inferred from DNA analysis showed Actinobacteria and Alphaproteobacteria as the most abundant and widespread bacterial taxa among the samples, followed by Chloroflexi and Firmicutes at specific sites. Archaea were mainly dominated by Nitrososphaerales, Methanobacteria, with the detection of other groups such as Halobacteria. Metaproteomics showed a high and even distribution of proteins involved in primary metabolic processes such as energy production and biosynthetic pathways, and a limited but remarkable presence of proteins related to resistance to environmental stressors such as radiation, oxidation, or desiccation. The results indicated that extra humidity in the system allows the microbial community to repair, grow, and prepare for the upcoming hyperarid period. Additionally, it supplies biomarkers to the medium whose preservation potential could be high under strong desiccation conditions and relevant for planetary exploration.